Identifikasi hubungan perilaku vandalisme dengan setting taman kota Lumintang, Denpasar, Bali - Ainun, Praga Balian; Mayun, Ida Ayu; Sugianthara, Anak Agung Gede (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Identification of relationship between vandalism behavior and setting of lumintang city park, Denpasar, Bali Province. Lumintang City Park Denpasar is one of the green open spaces visited by many people. The high intensity of visits leads to some problems, vandalism is one of them. This research aims to analyze the relevance of vandalism activity with environmental factors, study the relationship between vandalism in each setting and learn the appropriate management system to reduce and analyze the behavior of vandalism. Method used in this research was implemented with the technique of (1) observation, (2) questionnaire distribution, (3) literature study, and (4) data analysis.The results showed that the highest activity carried out was to dispose of the garbage is not in place and the highest object affected by vandalism activity is groundcover. Environmental factors that affect waste disposal activities are out of place, limited waste facilities, the presence of previous garbage and small waste bins, while the setting that affects the placement of facilities is not strategic or not in accordance with the point of gathering visitors.These problems can be upgraded by proper management of settings and facilities by looking at the factors that affect the activities of the vandalism.